Effect of Hypoproteinemia on Electrolyte Measurement by Direct and Indirect Ion Selective Electrode Methods - Gohel, Mukesh; Makadia, Jemil S.; Chakrabarti, Chandan (Journal of Laboratory Physicians, 2021)
Objective The aim of this study was to see the effect of hypoproteinemia on electrolyte measurement by two different techniques, that is, direct ion selective electrode (ISE) and indirect ISE.Material and Method It was an observational study in which 90 serum samples with normal protein content (Group-1) were subjected to sodium (Na+) and potassium (K+) measurements by direct and indirect ISE methods. In the same way, 90 serum samples with total protein < 5 g/dL (Group-2) were subjected to Na+ and K+ measurements by direct and indirect ISE methods.Result In samples from Group-1 patients, average Na+ was 138.1 ± 4.764 mmol/L by direct ISE method and 139.3 ± 3.887 mmol/L by indirect ISE method while average K+ was 4.41 ± 0.644 mmol/L by direct ISE method and 4.40 ± 0.592 mmol/L by indirect ISE method. There was no statistically significant difference in Na+ and K+ values measured by different methods. In samples from Group-2 patients, measured value of Na+ by direct ISE and indirect ISE was 134.57 ± 5.520 mmol/L and 138.64 ± 5.401 mmol/L, respectively. Difference between these two values was statistically significant with p-value of < 0.0001, but direct ISE and indirect ISE measured values of K+ was 4.146 ± 0.9639 mmol/L and 4.186 ± 0.8989, respectively, with no significant difference.Conclusion Direct and indirect ISE methods are not comparable and showing significantly different results for Na+ in case of hypoproteinemia. So, it is recommended that setups like intensive care unit or emergency department, where electrolyte values have significant treatment outcome, should follow direct ISE method and should compare its previous result with the same method. Both the methods should not be used interchangeably.
Keywords: ion selective electrode; electrolytes; sodium; potassium; hypoproteinemia